2018
DOI: 10.3390/gels4010014
|View full text |Cite
|
Sign up to set email alerts
|

Non-Conventional Methods for Gelation of Alginate

Abstract: This review presents and critically evaluates recent advances in non-conventional gelation method of native alginate. A special focus is given to the following three methods: cryotropic gelation, non-solvent induced phase separation and carbon dioxide induced gelation. A few other gelation approaches are also briefly reviewed. Results are discussed in the context of subsequent freeze and supercritical drying. The methods are selected so as to provide the readers with a range of novel tools and tactics of pore … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 61 publications
2
67
0
1
Order By: Relevance
“…We developed the fast release therapy through the bioprinting fixation ( Fig. 2a) followed by freeze gelation, using ethanol 19 (Fig. 2b), enabling the fabrication of 5D nano-laden hydrogel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We developed the fast release therapy through the bioprinting fixation ( Fig. 2a) followed by freeze gelation, using ethanol 19 (Fig. 2b), enabling the fabrication of 5D nano-laden hydrogel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cryogelation is a complex process and consists of three steps: non-deep freezing of a polymer solution, its storage in the frozen state, and thawing. The obtained cryogels are characterized by elasticity and a soft, porous structure with high permeability for drug molecules [11,12]. Tentative tests comparing the effect of solvent-casting and freeze-thaw method on placebo film characteristics showed that films formulated by freeze-thawing possessed significantly better mechanical, swelling, and mucoadhesive properties (data presented in Supplementary Materials).…”
Section: Resultsmentioning
confidence: 96%
“…Solvent crystallization during freezing might lead the polymer chains to connect into structures with a large number of macropores. ALG gels obtained using freeze-thaw method demonstrate a significant shrinkage that indicates a high degree of a balance between repulsive and attractive interactions, which, as a consequence, might lead to the creation of junction zones through Van der Waals forces and between uncharged ALG hydrogen bonds chains in the unfrozen liquid phase during thawing [10,11]. In our work, the OLG effect on the pharmaceutical characteristics of ALG buccal films was also examined.…”
Section: Introductionmentioning
confidence: 90%
“…Because amine groups in CS are protonated, repulsive electrostatic forces appear among different chains. Therefore, no attractive electrostatic interaction among polyelectrolytes takes part, and hydrogen bonding among chains becomes the main force, determining the gelation of the alginate [44,45], as well as the interaction among PEG and poloxamer with polyelectrolytes. Nevertheless, given that under high ionic strength conditions no aggregation was observed, despite the screening of charges, it is more likely that the denaturation of the BSA, which occurred at pH 2, is the triggering process [46].…”
Section: Discussionmentioning
confidence: 99%